2019
DOI: 10.1049/iet-pel.2018.5680
|View full text |Cite
|
Sign up to set email alerts
|

Novel three‐level T‐type isolated bidirectional DC–DC converter

Abstract: This study presents a novel three-level T-type isolated bidirectional DC-DC converter (3LTT-IBDC) for bidirectional DC power transfer. Owing to of the T-type structure of the proposed converter it has less number of switches and thus, lower cost and higher efficiency, as well as easy control are the advantages of the proposed converter compared to three-level counterparts. Additionally, 3LTT-IBDC is more reliable than three-level converters since unequal voltage blocking does not occur in T-type structure. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 25 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…2(a) will be analyzed as a comparative topology in this section. Meanwhile, according to (7) and (8), it can be observed that the voltage gain of LLCL is directly affected by the transformer turns-ratio, quality factor, and the resonant inductance ratios, which is similar to the other LLC-type resonant converters. Hence, these variables that reflect the converters' working conditions will be considered in the comparisons.…”
Section: B Resonant Tank Analysismentioning
confidence: 69%
See 3 more Smart Citations
“…2(a) will be analyzed as a comparative topology in this section. Meanwhile, according to (7) and (8), it can be observed that the voltage gain of LLCL is directly affected by the transformer turns-ratio, quality factor, and the resonant inductance ratios, which is similar to the other LLC-type resonant converters. Hence, these variables that reflect the converters' working conditions will be considered in the comparisons.…”
Section: B Resonant Tank Analysismentioning
confidence: 69%
“…By means of (2), (6), Fig. 9, and Kirchhoff's current/voltage laws, the dc voltage gain of LLCL in forward mode (MF) and backward mode (MB) can be deduced as (7) and 8…”
Section: A DC Voltage Gain Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The converter was operated under zero voltage switching but it is limited to a unidirectional operation only. For bidirectional operations, another half‐bridge T‐type DC‐DC converter is added to the secondary side of the high‐frequency transformer as proposed in [27]. Further development has seen a full‐bridge T‐type DC‐DC converter topology that was proposed to improve the power handling capability with a wider input voltage range but at the expense of more power switches [28, 29].…”
Section: Introductionmentioning
confidence: 99%